Delving into the eye of the cyclone to quantify the cascading impacts of natural disasters on life satisfaction - Ha Trong Nguyen; Francis Mitrou (Global Labor Organization (GLO), 2024)
The catastrophic effects of natural disasters on social and economic systems are well-documented; however, their impacts on individual life satisfaction remain insufficiently understood. This study pioneers a causal analysis of cyclones' impacts on Australians' life satisfaction, using local cyclones as natural experiments. Analysing over two decades of data, individual fixed-effects models reveal that cyclones, particularly category 5 (highest severity) cyclones in close proximity to residences, significantly reduce overall life satisfaction and specific domains like community, personal safety, and health satisfaction. Notably, these cyclones have a lasting impact on community and personal safety satisfaction. Our findings withstand rigorous sensitivity assessments, including a falsification test demonstrating no impact of future cyclones on current life satisfaction. Moreover, extensive heterogeneous analysis uncovers significant variations in cyclone impact based on life satisfaction domains and individual, household, and regional characteristics. Additionally, this study shows that cyclone-induced home damage, especially from the most severe cyclones, significantly diminishes the aforementioned life satisfaction outcomes, but to a much greater magnitude.
Keywords: I12; I31; R23; Q54; 330; Natural Disasters; Life Satisfaction; Happiness; Wellbeing; Australia